Preoperative Nutritional Status and Risk Factors Associated with Delayed Discharge in Geriatric Patients Undergoing Gastrectomy: A Single-Center Retrospective Study - Xining Zhao; Jie Liu; Ying Wang; Yuying Yang; Yan Pan; Shengjin Ge (Applied Bionics and Biomechanics)
Objective. Preoperative malnutrition is an independent risk factor for postoperative complications and survival for gastric cancer patients. The study is aimed at investigating the prevalence of malnutrition, perioperative nutritional support, and the risk factors associated with delayed discharge of geriatric patients undergoing gastrectomy. Methods. A retrospective study of gastric cancer patients (age≥65) who underwent gastrectomy at Zhongshan Hospital from January 2018 to May 2020 was conducted. Clinical data, including demographic information, medical history, surgery-related factors, and perioperative nutritional management, were collected and analyzed. Postoperative complications were assessed according to the Clavien-Dindo grading system, and the prognostic nutritional index (PNI) was calculated. The risk factors affecting the prolongation of postoperative hospital stay were analyzed. Results. A total of 783 patients were reviewed. The overall frequency of malnutrition was 31.3% (249/783). The albumin, prealbumin, and hemoglobin levels were lower in the malnutrition group than in the well-nourished group. The proportion of patients who received preoperative total parenteral nutritional support in the malnutrition group was significantly higher than in the well-nourished group (12.4% vs. 3.7%, P<0.001). All patients received postoperative parenteral nutrition (PN); the proportion of patients who received total nutrient admixture (TNA) in the malnutrition group was lower than in the well-nourished group (22.1% vs. 33.5%, P=0.001). No significant difference was found in the duration of postoperative nutrition between groups (P>0.05). The malnutrition group was associated with a higher rate of postoperative complications (P<0.001). Univariate and multivariate regressions revealed that age>70 years (OR=1.216, 95% CI 1.048-1.411, P=0.010), operation time>180 min (OR=1.431, 95% CI 1.237-1.656, P<0.001), PNI<44.5 (OR=1.792, 95% CI 1.058-3.032, P=0.030), and postoperative complications (OR=2.191, 95% CI 1.604-2.991, P<0.001) were significant risk factors associated with delayed discharge. Conclusion. Malnutrition is relatively common in elderly patients undergoing gastrectomy. Advanced age, duration of surgery, lower levels of PNI, and postoperative complications were risk factors associated with delay discharge. Elderly gastric cancer patients with risk factors urgently require specific attention for reducing hospital stay.